Perencanaan Penggunaan Metode Analytical Hierarchy Process (AHP) Pada Pemilihan Supplier Di PT FKI - Febry Rizki Putra Henry Wirama; Puji Isyanto; Dini Yani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This report aims to plan the use of the Analytical Hierarchy Process (AHP) method in selecting suppliers at PT FKI through observation as well as initial data collection. In practice, the practitioner carries out practical work in the purchasing department with the main tasks, namely: the process of purchasing requests, the process of finding and selecting suppliers, and the purchase order process, so that the practitioner is responsible for and involved in the purchasing department and studies the supplier selection process, including the criteria used to assess and choose a supplier. The results of observations at PT FKI show that when supplier selection does not use a method, this can lead to some negative consequences, so the practitioner advises PT FKI to use a structured method such as the Analytical Hierarchy Process (AHP) method because this method can assign weights to each criterion and compare suppliers objectively.